Effect of Nutrient Management on Two Varieties (Hybrid and Local) of Maize in Western Inner Terai of Nepal - Bashyal, Shila; Poudel, Padam Bahadur; Magar, Jenny Budha; Dhakal, Laxmi; Chad, Suraj; Khadka, Binita; Bohara, Sidda Lal (International Journal of Applied Sciences and Biotechnology, 2020)
In Nepal, the productivity of maize is very low in comparison with developed countries. The use of hybrid varieties with proper nutrient management helps to unlock the high yielding potential of maize. So, the experiment was conducted at Fulbari, Dang, Nepal from June 30, 2019 to October 16, 2019 to find the yield performance of two maize varieties (Local and Hybrid) under different nutrient management. The study was conducted in factorial randomized complete block design with three replications and eight treatments. Treatments consist of different combinations of two maize varieties (Local and hybrid) and four different nutrient management practices. Significant effects of Nutrient management were observed on plant height, leaf area index (LAI), kernels per row, kernels per cob maize, test weight, biological yield, economic yield and harvest index of maize. Similarly, significant effects of varieties was observed on plant height, leaf number, LAI, cob length, kernel rows per cob, kernels per kernel row, kernels per cob maize, test weight, biological yield, economic yield and harvest index of maize. Interaction effect of Nutrient management and varieties was found significant on LAI, kernel rows per cob, kernels per kernel row, kernels per cob maize, test weight, biological yield, economic yield and harvest index of maize. The overall performance of hybrid maize under Leaf color chart (LCC) based nutrient management was found better than other treatments. Therefore, production of Hybrid maize under LCC based nutrient management is suggested.Int. J. Appl. Sci. Biotechnol. Vol 8(2): 191-198